An in vitro investigation of fluoroquinolones on glycaemic pharmacological targets - Katshaza, Oyisa Sisipho Hope (Rhodes University, 2026)
In 2021, over 537 million adults worldwide (ages 20–79) had diabetes mellitus (T2DM), with numbers expected to rise to 643 million by 2030 and 783 million by 2045. T2DM makes up 90–95% of cases, primarily driven by obesity, sedentary lifestyles, and ageing. Oral antidiabetic treatments are effective initially but lose efficacy as beta cell failure progresses, making insulin therapy necessary to maintain normoglycemia. Additionally, these treatment options have numerous side effects such as gastrointestinal disturbances, hypoglycaemia, weight gain, diarrhoea, and abnormal liver function. A class of antibiotics, fluoroquinolones, has been shown to exert hypoglycaemia as a side effect. Fluoroquinolones show potential for diabetes treatment due to their cost-effective production, high oral absorption, and strong tissue penetration. Their dual oral and intravenous availability supports flexible treatment. This study aimed to explore the potential glucose-lowering properties of four fluoroquinolones. They were investigated for their potential inhibitory activity on carbohydrate-hydrolysing enzymes. and for effects on target cells (skeletal muscle and liver cells).
Keywords: Diabetes (http://id.loc.gov/authorities/subjects/sh85037456); Fluoroquinolones (http://id.loc.gov/authorities/subjects/sh2012000857); Glucose (http://id.loc.gov/authorities/subjects/sh85055360); Insulin (http://id.loc.gov/authorities/subjects/sh85066794); Enzyme inhibition (https://www.wikidata.org/wiki/Q5381546); Insulin signaling (https://www.wikidata.org/wiki/Q30225566)